RES IPSA LOQUITUR: APPLICATION IN PRODUCT LIABILITY - Putri, Windy Virdinia; Muhammad, Danang Wahyu (Faculty of Law Universitas Padjadjaran, 2023)
Consumers who experience loss, injury, or death due to a damaged or defective product can claim compensation. However, the difficulty of proof is a scourge for consumers. In law, the doctrine of res ipsa loquitur was introduced, which in English means that things speak for itself. Based on the doctrine, the law presumes a presumption of negligence which can then be applied to the reverse burden of proof. This study examines the principle of product responsibility in the Consumer Protection Act and the application of the res ipsa loquitur doctrine in product liability. This research is normative research using a conceptual approach and a statute approach. This study found that the principle of product liability in the Consumer Protection Act contains two principles: first, the presumption of negligence, and second, the presumption of liability principle with the burden of proof reversed. In line with the consumer interest-oriented doctrine, res ipsa loquitur also contains the presumption of negligence followed by the presumption of liability principle. The application of the res ipsa loquitur doctrine in product liability is found in 2 things: first as a principle and second as a means of evidence in civil procedural law which can be enforced through evidence of a presumption concluded by a judge.